Multisystem inflammatory syndrome in children after vaccination against SARS-COV-2 (International Seven Journal of Multidisciplinary, 2023)
COVID-19 in some children has caused serious consequences, such as multisystem inflammatory syndrome in children (MIS-C). Since December 2020, the mRNA vaccine against SARS-CoV-2 has been available with a good safety profile. However, evidence on safety and vaccination strategies in children with MIS-C is still lacking.